2007
DOI: 10.1177/1440783307073935
|View full text |Cite
|
Sign up to set email alerts
|

The resistible rise of Islamophobia

Abstract: This article compares the rise of anti-Muslim racism in Britain and Australia, from 1989 to 2001, as a foundation for assessing the extent to which the upsurge of Islamophobia after 11 September was a development of existing patterns of racism in these two countries. The respective histories of immigration and settlement by Muslim populations are outlined, along with the relevant immigration and ‘ethnic affairs’ policies and the resulting demographics. The article traces the ideologies of xenophobia that devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(53 citation statements)
references
References 15 publications
2
51
0
Order By: Relevance
“…These findings are in line with past research which has acknowledged the impact of Islamophobia on Muslim employment in Australia (Colic-Peisker & Tilbury, 2007;Poynting & Mason, 2007). Statistics from 2001 (Tilbury, 2007) reported that the unemployment rate for Australian Muslims was significantly higher than the unemployment rate for all Australians.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These findings are in line with past research which has acknowledged the impact of Islamophobia on Muslim employment in Australia (Colic-Peisker & Tilbury, 2007;Poynting & Mason, 2007). Statistics from 2001 (Tilbury, 2007) reported that the unemployment rate for Australian Muslims was significantly higher than the unemployment rate for all Australians.…”
Section: Discussionsupporting
confidence: 80%
“…ColicPeisker and Tilbury's (2007) investigation into the effect of visible difference on employment found that African minority groups (from Somalia, Sudan, Ethiopia, and Eritrea) suffered high levels of unemployment based on race, religion, and ethnic origin, with multiple narratives reflecting racial discrimination in the workforce. Other Australian studies have also found that unemployment and underemployment is a problem among Muslims in Australia as a whole (Constable, Wagner, Childs, & Natoli, 2004;Guerin, Guerin, Diirye, & Abdi, 2005;Poynting & Mason, 2007;Tilbury, 2007). The next section provides an overview of Somali visible difference due to external religious markers.…”
Section: Visible Differencementioning
confidence: 99%
See 1 more Smart Citation
“…Cultural racism was challenged through greater self-pride and an interest in global anti-racist movements. Thus people like Muhammad Ali, Malcolm X, Nelson Mandela and even the PLO leader Yasser Arafat entered our family domain through the medium of global communications (Saeed, 2014a,b;2007;. Whilst the AfricanAmerican, South African and Palestinian histories (Drainville and Saeed, 2013; have their own stories, what became evident were the common threads of racism, imperialism and exploitation.…”
Section: Encountering Racismmentioning
confidence: 99%
“…Years later, the Labour Prime Minister Gordon Brown would echo a neofascist slogan and lament 'British jobs for British workers' (Saeed, 2010;2007). More recently the current Labour leader has promised to tighten immigration laws and protect 'British workers' (BBC, 2014).…”
Section: Encountering Racismmentioning
confidence: 99%